Vaccine fatigue and influenza vaccination trends across Pre-, Peri-, and Post-COVID-19 periods in the United States using epic’s cosmos database - Tyler B. Nofzinger; Timothy T. Huang; Christopher Eduard R. Lingat; Gaurang M. Amonkar; Emily E. Edwards; Albert Yu; Alexander D. Smith; Nasser Gayed; Heidi L. Gaddey (PLoS ONE, 2025)
Introduction Influenza vaccination is a critical public health measure, especially amidst the challenges of the COVID-19 pandemic. This study uses Epic’s Cosmos database to analyze influenza vaccination trends across demographic groups in the United States, examining the effects of the COVID-19 pandemic and “vaccine fatigue” on influenza vaccination rates. Methods This retrospective cross-sectional study analyzes influenza vaccination rates pre- (1 May 2018–31 May 2019), peri- (1 May 2020–31 May 2021), and post-COVID-19 (1 May 2023–31 May 2024). A two-proportion z-test and Cohen’s h test were calculated to assess statistical significance. Results Influenza vaccination rates increased peri-COVID (+1.99% point change, h = 0.04, p < 0.001) and decreased post-COVID (−6.41% point change, h = 0.14, p < 0.001) relative to pre-COVID. The largest changes were observed in the following groups: 5−18 year olds (−13.92% point change, h = 0.31, p < 0.001), 19−26 year olds (−9.91% point change, h = 0.25, p < 0.001), American Indian or Alaska Native (−8.11% point change, h = 0.18, p < 0.001), Other Races (−7.36% point change, h = 0.17, p < 0.001), White (−6.89% point change, h = 0.15, p < 0.001), and the South U.S. census region (−7.21% point change, h = 0.17, p < 0.001). Conclusion Post-pandemic influenza vaccination compliance decreased relative to pre-pandemic, especially among younger age groups, certain racial groups, and in the southern U.S. These findings suggest that the COVID-19 pandemic negatively impacted influenza vaccination compliance. While overall trends aligned with publicly available data, absolute counts may be under-reported within Epic due to incomplete documentation of vaccine administrations outside of Epic-affiliated systems.